Role of Paracoccidioides brasiliensis cell wall fraction containing beta-glucan in tumor necrosis factor-alpha production by human monocytes: correlation with fungicidal activity - Anjos, A. R.; Calvi, S. A.; Ferracini, R.; Peracoli, MTS; Silva, C. L.; Soares, AMVC (B I O S Scientific Publishers Ltd, 2002)
The polysaccharide fraction of Paracoccidioides brasiliensis mycelial cell wall (F1 fraction), the active component of which is composed of beta-glucan, was investigated in regard to the activation of human monocytes for fungal killing. The cells were primed with interferon-gamma (IFN-gamma) or F1 (100 and 200 mug ml(-1)) or F1 (100 and 200 mug ml(-1)) plus IFN-gamma for 24 h and then evaluated for H2O2 release. In other experiments, the cells were pretreated with the same stimuli, challenged with a virulent strain of P. brasiliensis and evaluated for fungicidal activity and levels of tumor necrosis factor (TNF-alpha) in the supernatants. F1 increased the levels of H2O2 in a similar manner to IFN-gamma. However, a synergistic effect between these two activators was not detected. on the contrary, a significant fungicidal activity was only obtained after priming with IFN-gamma plus F1. This higher activity was associated with high levels of TNF-alpha in the supernatants of the cocultures. Overall, P. brasiliensis F1 fraction induced human monocytes to release relatively high levels of TNF-alpha, which, in combination with IFN-gamma, is responsible for the activation of human monocytes for effective killing of P. brasiliensis.
Keywords: beta-glucan; fungicidal activity; monocyte; Paracoccidioides brasiliensis; TNF